The consumer cooperative movement. A social interpretation. - W.J. Campbell. A factual survey. Rev. and repr (The League for Industrial Democracy, 1940)
With notes and refs. L.I.D. Pamphlet series. 1st ed. titled: Consumers' cooperation.